Application of E-Government in Efforts to Improve Public Services (Study in Papua Province) - Aldrin Watson Gainau (Formosa Journal of Applied Sciences, 2023)
This study aims to discuss the implementation of e-government in the era of special autonomy in Papua as an effort to improve the quality of public services. The method used is through a library approach. Data were obtained from various literature sources relevant to the research topic, then data analysis was carried out in several stages; reduction, presentation, conclusion and verification. The results of this study indicate that the implementation of e-government for the Provincial Government of Papua can be used as a new model both in leadership style, policy making, new means of responding to public complaints, public accountability, including in administration and service management, as well as a forum for outreach to the community based on achievements. good governance.